STUDY ABOUT THE USAGE OF FLY ASH WASTE IN THE MANUFACTURE OF COMPOSITE MATERIALS WITH RUBBER MATRIX - Sabin Cristinel DIMULESCU; Mihaela WETTERNEK (Fiabilitate şi Durabilitate)
In the current background of excessive usage of plastic and rubber materials, hardly degradable, when the pollution level and global warming problems due to industrialization are rising, the world turns to new materials, especially composites, with a low impact on the environment, and to using waste formed from other fabrication processes and which after the termination of their life cycle to be easily recycled and reused in the manufacturing of new products with very good qualities.